2020
DOI: 10.1097/jsm.0000000000000623
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of the Surgical and Rehabilitative Outcomes of Hip Arthroscopy in Athletes With Femoroacetabular Impingement

Abstract: The majority of athletes return to sport after hip arthroscopy for symptomatic FAI. Severity of intraarticular damage and degree of degenerative changes affect ability to return to sport. Additional validated outcome measures should be used together with return to sport. Future studies should be prospective with longer-term follow-up to provide a higher level of evidence for outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Multiple studies reported a return-to-sport rate of .80% in recreational and 46 (2012) professional athletes. 7,33,45,57 Similarly, our systematic review found a collective return-to-sport rate of 84.9% in adolescents. We suggest that in addition to favorable hip function, an adolescent's passion for the sport and the vast social benefits of returning to sport motivate an adolescent athlete to return to play.…”
Section: Discussionsupporting
confidence: 59%
“…Multiple studies reported a return-to-sport rate of .80% in recreational and 46 (2012) professional athletes. 7,33,45,57 Similarly, our systematic review found a collective return-to-sport rate of 84.9% in adolescents. We suggest that in addition to favorable hip function, an adolescent's passion for the sport and the vast social benefits of returning to sport motivate an adolescent athlete to return to play.…”
Section: Discussionsupporting
confidence: 59%
“…When obtaining long-term follow-up in athletes who underwent arthroscopic FAI surgery to calculate the rate of return to sport, athletes who had unsuccessful outcomes should be investigated in detail and reported in the study. As of now, there is inconsistency in the literature regarding the definition of “return to sport.” 7,19,28 For example, an athlete who returned to sport at a lower level of competition might or might not have been calculated as having not returned to sport, depending on the study design. Similarly, some athletes could return to a different type of sport from the one in which they were participating before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…7,14 The rate of return to sport after this procedure in recreational and high-level athletes ranges between 80% and 100%. 7,19,28 Factors that are associated with a higher rate of return to sport in athletes undergoing arthroscopic FAI surgery include younger age, shorter duration of symptoms, relatively maintained hip function, and absence of severe cartilage damage. 7,23,40 However, some patients do not wish to return to physical activity after surgery for reasons unrelated to their hip.…”
mentioning
confidence: 99%
“…Six recent systematic reviews have examined RTS levels following surgical management of hip-related pain. The synthesis of these pooled findings determined that between 86% and 93% of athletes return to sport participation 49 56–60. However, the actual level of RTS of these athletes is mostly unreported, with only one-third of included studies clearly distinguishing RTS (any level) from RTS at preinjury level 56.…”
Section: Discussionmentioning
confidence: 99%